Sun exposure behavior and protection practices in a Mediterranean population: a questionnaire-based study - Nikolaou, V; Stratigos, A. J.; Antoniou, C.; Sypsa, V; Avgerinou, G.; Danopoulou, I.; Nicolaidou, E.; Katsambas, A. D. (Photodermatol Photoimmunol PhotomedPhotodermatol Photoimmunol PhotomedPhotodermatol Photoimmunol Photomed, 2009)
OBJECTIVE: Skin cancer campaigns have only recently been implemented in a wide scale in Greece. In order to better target those individuals at risk, we aimed to explore sun exposure behaviors in a sample of the Greek population. METHODS: A total of 802 subjects, randomly selected among the residents of the two largest Greek cities, underwent a questionnaire-based telephone interview, assessing the degree of sun exposure patterns and knowledge of skin cancer risk factors. RESULTS: Females more commonly (90%) used sunscreens compared with males (67.5%), and among sunscreen users, only 8% used products with SPF <10. Almost half of the participants (48%) preferred going to the beach during the midday hours. Over exposure to the sun was mostly reported by individuals with phototypes III/IV and of younger age (18-35 years). Most participants were aware of sun exposure as a cause of skin cancer, but among those who did not, 41% were younger than 34 years of age. CONCLUSIONS: In our survey, significant differences in age, sex and phototypes were observed with regard to sun exposure patterns and sunscreen use. Educational campaigns should focus more on younger age groups, encouraging a more complete set of photoprotective measures. However, potential trial limitations inherent in self-reported measures should be taken into account.
Keywords: *Environmental Exposure; *Health Behavior; *Health Knowledge, Attitudes, Practice; *Sunlight; Adolescent; Adult; Female; Greece; Humans; Male; Risk Factors; Skin Neoplasms/*prevention & control; Sunscreening Agents; Surveys and Questionnaires; Young Adult